A Systematic Review of Leadership Strategies for Enhanced Technology Usage Among Teachers in Secondary Schools - Sulaimon Adewale (Interdisciplinary Journal of Education, 2025)
Despite the inestimable benefits of technology use in the 21st century, there is still an apparent digital divide in technology use based on gender in all spheres of life. The onus of this study is to systematically review relevant strategies adopted by secondary school leaders to achieve enhanced technology acceptance and usage, especially among female teachers. Also, to determine its implications for education leadership and management. With the aid of the PRISMA protocol, 499 articles identified were painstakingly analysed. These articles were obtained from Scopus and Web of Science Digital bases. Only 20 articles that fulfilled the relevance and quality eligibility criteria were included in the review for analysis. It was found that there was a paucity of studies on leadership strategies adopted by secondary school principals to enhance technology usage among teachers in secondary schools. Similarly, eight leadership strategies were identified as the common ones among secondary school principals to integrate and enhance technology usage in their various schools globally. This study uniquely assembled various exemplified strategies for technology integration, which will likely be helpful for school leaders who are yet to successfully integrate technology usage into the hearts of teachers in their various schools.